The Potential Role of the Dipeptidyl Peptidase-4-Like Activity From the Gut Microbiota on the Host Health - Olivares, Marta; Schüppel, Valentina; Hassan, Ahmed M.; Beaumont, Martin; Neyrinck, Audrey M.; Bindels, Laure B.; Benítez-Páez, Alfonso; Sanz, Yolanda; Haller, Dirk; Holzer, Peter; Delzenne, Nathalie M. (Frontiers in Microbiology, 2018)
The dipeptidyl-peptidase-4 (DPP-4) activity influences metabolic, behavioral and intestinal disorders through the cleavage of key hormones and peptides. Some studies describe the existence of human DPP-4 homologs in commensal bacteria, for instance in Prevotella or Lactobacillus. However, the role of the gut microbiota as a source of DPP-4-like activity has never been investigated. Through the comparison of the DPP-4 activity in the cecal content of germ-free mice (GFM) and gnotobiotic mice colonized with the gut microbiota of a healthy subject, we bring the proof of concept that a significant DPP-4-like activity occurs in the microbiota. By analyzing the existing literature, we propose that DPP-4-like activity encoded by the intestinal microbiome could constitute a novel mechanism to modulate protein digestion as well as host metabolism and behavior.